Polymorphic loci of the ESR1 gene are associated with the risk of developing preeclampsia with fetal growth retardation - O. V. Golovchenko; M. Yu. Abramova; I. V. Ponomarenko; M. I. Churnosov (Акушерство, гинекология и репродукция, 2021)
Aim: to analyze the association of the ESR1 gene polymorphic loci rs2234693, rs9340799, and rs3798577 with developing preeclampsia (PE) with fetal growth retardation (FGR). Materials and Methods. The study was performed while analyzing a sample of 400 women: 76 pregnant women with PE and FGR and 324 with a physiological course of pregnancy. Three polymorphic loci of the ESR1 gene (rs2234693, rs9340799, and rs3798577) were genotyped. Functional effects of polymorphic loci were evaluated by using the online programs HaploReg (epigenetic effects) and GTEx Portal (relation to gene expression). Results. The development of PE and FGR is associated with the G allele and GG genotype rs9340799 of the ESR1 gene (OR = 1.38; pperm = 0.04 and OR = 2.00; pperm = 0.04, respectively), the T allele rs3798577 of the ESR1 gene (OR = 1.46; pperm = 0.01), and the TG haplotype of the polymorphic loci rs2234693–rs9340799 of the ESR1 gene (OR = 2.08; pperm = 0.009). Polymorphic locirs2234693, rs9340799 ESR1 gene and rs3798577 have an important functional significance in human body being located in the evolutionarily conserved DNA region, affect affinity of regulatory DNA motifs to the eight transcription factors as well as ESR1 gene expression in the thyroid gland, which are positioned in the promoter and enhancer region, DNAse 1 hypersensitivity motif within diverse organs and tissues, and display an important pathogenetic effect for development of PE and FGR. Conclusion. Polymorphic loci rs2234693, rs9340799 and rs3798577 of the ESR1 gene are associated with developing PE and FGR.